P14.73 Toxicity and outcomes of reduced-dose whole brain radiotherapy as consolidation treatment for patients with CNS lymphoma in real life setting. (6th September 2019) - Lesueur, P; Damaj, G; Hoang-Xuan, K; Rolland, V; Schmitt, A; Chinot, O; Fabbro, M; Agapé, P; Chabrot, C; Chebrek, S; Feuvret, L; Stefan, D; et al.
Abstract: BACKGROUND: Optimal treatment strategy for newly diagnosed primary PCNSL remains controversial. The high risk of radio-induced late-delayed neurotoxicity in patients who achieve long-term disease control constrains the use of classical consolidation WBRT. So as to reduce side cognitive effects, Morris et al, reported a phase II study, to assess the efficacy and toxicity of consolidation reduced-dose (23.4Gy) WBRT (rdWBRT) for patients with complete response after high dose methotrexate based chemotherapy. The study reported a 2-year PFS rate for these patients of 77%, with no evidence of significant cognitive decline during the follow-up (FU) period. The aim of this retrospective study was to report toxicity and outcomes of rdWBRT, in patients < 60 years old with complete response (CR) after HD-MTX based chemotherapy, in real life setting, without selection bias. MATERIAL AND METHODS: Patients were selected from the French LOC network database, a nationwide database centralizing since 2011 information from 28 different centers in France, representing the main centers involved in PCNSL management. Patients were retrospectively selected according to the following criteria: 1) Pathological diagnosis of diffuse large B cell PCNSL; 2) age>18 and <60 years; 3) immunocompetent status; 4) First line induction treatment based on high dose MTX (At least MTX>1.5 g/m2); 5) CR according to the IPCG criteria after first-line induction treatment. Patients should have received a rdWBRT (23.4Gy in 13 fractions of 1.8Gy). RESULTS: Twenty seven patients, were included. The median FU from initial diagnosis was 28.5 months [9.6–50.7]. Median age was 50.2 years [25–60]. Median Karnofsky Performans Status (KPS) was 90% [40–100%]. Seventeen patients had a multi focal disease at diagnosis (meningeal involvement n=6, in ophthalmic involvement n=4). PFS rates were 85% IC95[76–100 %], 65% IC95 [45–85%] and 65% IC95 [45–85%] at 1, 2, and 3 years respectively. The OS rates were 100%, 90, 5% IC95 [77–100%] and 85%IC95 [69–100%]. 8 patients relapsed, with a median time from radiotherapy to recurrence of 6.5months [2.4–17]. All recurrences were outside the initially involved site(s), and 62.5% of tumors recurred as multifocal disease. All patients received salvage treatment, including intensive chemotherapy with autologous stem cell transplantation in 4 cases. No acute grade III-IV toxicity related to rdWBRT was reported. Neuropsychological follow up was available for 14 patients with no cognitive impairment at last follow up. CONCLUSION: This is the largest retrospective study evaluating outcomes of rdWBRT for PCNSL young patients with CR after HD-MTX chemotherapy. Real life setting data from this study are quite reassuring, and rdWBRT could be considered as an efficient and safe consolidation strategy in this population. We need a longer FU to confirm the absence of cognitive deterioration.